Innovative Strategies to Prevent Childhood Smoking Epidemic: Systematic Review - Ahsanu Bil Husna; Ira Nurmala; Nendy Putra Salsabila (Jurnal Promkes: The Indonesian Journal of Health Promotion and Health Education, 2024)
Background: The phenomenon of smoking in children is a serious problem. There are still many minors who smoke and traders who still sell cigarettes to them. Although regulation regarding this issue has been established, legal attention to this problem is still fairly minimal; this shows the need for law enforcement and further protection for children. The rate of e-cigarette use among children aged 13–15 years is higher than adults across WHO regions. Aims: This research aimed to determine how efforts have been made to reduce smoking prevalence in children. Method: This literature study used a Systematic Literature Review (SLR).  PubMed, Science Direct, ResearchGate, and Google Scholar were used for the literature search. The keywords used were "Child Smoking," or "Child Cigarettes" and "Smoking Policy" or "Child Smoker". Results: Several efforts were made to reduce the prevalence of smoking in children, including legal protection efforts related to cigarette advertising regulations, restriction on cigarette dealers, prevention on selling cigarettes to children, expanding the implementation of KTR, providing smoking cessation services for children, mass campaigns and education for children, improving fiscal policy, and making innovation such as "Smoking Prevention in School Children in Hospitals" program and an idea called cigarette vending machine. Conclusion: Regulations related to cigarette use must continue to be pursued and implemented according to standards following local government policies by paying attention to the principles and guidelines provided. Families also play a role in helping to prevent the initiation of smoking in children.